Knowledge, Attitude and Practice of Mothers Towards Newborn Care in Jugal Hospital, Harari Regional State, Ethiopia - Jamie, Arif Hussen; Amin, Rafika (Journal of Nepal Paediatric Society, 2021)
Introduction: Globally every year about four million neonates die in the first 28 days of life and similar number of babies is stillborn. Most neonatal deaths (99%) occur in low income and middle-income countries. The global neonatal mortality rate is 18,  in Africa it is 26.7 and  in Ethiopia, it is 30 per 1000 live births in 2019. In Ethiopia, neonatal mortality remains high and accounts for about half of the under-five mortality. There are relatively fewer studies regarding knowledge, attitude and practice of mothers towards newborn care in Ethiopia. However, no such study has been done in Harari region. So, this study was planned to assess the knowledge, attitude and practice of newborn care among postnatal mothers in Harari regional state, Ethiopia.     Methods: An institutional based cross-sectional study was conducted among postnatal mothers who were randomly selected from Jugal hospital. A systematic random sampling method was followed. A pre-tested questionnaire was used. Data was entered, cleaned and analysed using SPSS version 20.Results: A total of 414 postnatal mothers were interviewed with a response rate of 98.1%, among them 74% had good knowledge, 77.14% had positive attitude and 65.45% had good practice of newborn care.Conclusions: This study indicated that nearly half and above respondents had good knowledge, positive attitude and good practice of newborn care, but a substantial number of postpartum mothers had poor knowledge and practice on newborn care in Harari Region. Therefore, provision of information, education and communication and regular training and workshops about newborn care should be done to  health professional working at MCH unit in order to increase the awareness of mothers through health education.